Interaktif Augmented Reality Sebagai Media Promosi Penjualan Perumahan - Dwi Saras Wati; Anang Kukuh Adisusilo; Beny YV Nasution (Melek IT : Information Technology Journal, 2016)
Development of the business world, especially the field of residential property in Indonesia is increasingly widespread. The development is influenced by several factors, one of them for the needs of the consumer. In response to the developers started to offer housing in various ways, such as print and electronic media, not infrequently through 2D sketches. In fact, the promotion through print media such as brochures on interactive less flavor because they have a limited viewing angle so that potential buyers puzzled to imagine a picture or shape of the house to be built. Therefore we need a media house marketing with the concept of interactive digital marketing media such as Augmented Reality. Augmented Reality is intended to produce Object Three Dimensional (3D) in accordance with the Real Estate and Housing Brochure media Changing housing promotion using interactive brochure. So in addition it also is appropriate to provide insight to the property developers in the field of marketing. Results of testing applications on android system can run well, and the results of trials in the housing marketing office puri safira Surabaya regency showed a percentage of more than 70% chose interested in using applications that have been tested for the model selection castle housing safira regency.